VACCINE DEVELOPMENT & MODERN APPROACHES FOR COVID 19 - Rakshit, Soumya; Bhattacharya, Sabuj Kumar; Mallik, Souvik; Mondal, Partha Sarathi; Acharya, Shibam; De, Sanjoy; Nandy, Bankim Chandra (Journal of Biomedical and Pharmaceutical Research, 2021)
Most of the infectious diseases due to pathogens are caused by the mucosal tract penetration. Hence, vaccines delivered directly to the mucosal tissues can defend pathogenic infections and provide protection at the first site of infection. Thus, mucosal, specifically, oral delivery is becoming the most ideal mode of vaccination. However, oral vaccines have to overcome numerous barriers such as the extremely low pH of the stomach, the presence of proteolytic enzymes and bile salts as well as low permeability in the intestine. Several formulations based on nanoparticles like liposomes, solid solutions, emulsions, VLPs are currently being used to prepare stable oral vaccine formulations. In current days different companies are trying to develop oral vaccine for COVID 19 also. This review briefly discusses several vaccine development criteria their mechanisms and various aspects of oral nanoparticles-based vaccine design that should be considered for improved mucosal and systemic immune responses. Keywords: Vaccine development, nanoparticles, liposome, VLP, COVID 19, mucosal immunity.